The Effect of Problem-Based Learning on Learning Outcomes of Pendidikan Agama Islam - Taufiqur Rahman; Moh. Zamili; Salma Munawwaroh (Program Pascasarjana Universitas Ibrahimy, 2021)
This study aimed to analyze and describe instructions applying problem-based learning in school. The research design is a systematic literature review conducted in seven steps. Data searched and retrieved from google scholar. Eligibility criteria for selected studies are articles published between 2017-2021 and written in the Indonesian language. This study concluded that applying problem-based learning in instruction positively affects learning outcomes, especially problem solving and critical thinking ability. PBL steps commonly used in classrooms are the teacher planning the lesson, stating the learning objectives, explaining the subject matter, dividing the group, students carrying out investigations, the teacher providing feedback. These steps are more of a learning activity than a sequence of learning activities.